IMPACT OF ARGON GAS SHIELDING FLOW RATE ON THE HARDNESS OF WELD JOINT - Abd Rahman, M.N.; Zulkipli, N.H.; Kasim, M.S.; Jamli, M.R.; Budi, E. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
Metal inert gas (MIG) welding technique is one of the most widely utilized permanent metal joining technique in various applications due to its adaptability towards automation. One of the critical process parameters in MIG is shielding gas flow rate. One of the main purposes of shielding gas is to prevent the formation of oxidation and porosity at the weld pool. However, study on the optimum level of shielding gas flow rate is lacking. This study investigated the impact of argon gas flow rate, as a shielding gas, on the weld zone hardness of a 3 mm thick mild steel plate. The flow rates of argon shielding gas were evaluated at five levels (0 SCFH, 15 SCFH, 30 SCFH, 45 SCFH, and 60 SCFH). Vickers hardness test was performed and an optical micrograph was captured for all samples. One-way ANOVA analysis was conducted to ascertain the statistical difference of hardness among the samples at a 95% confidence level. The results indicated that the argon flow rate has a significant positive impact on the hardness of the weld zones as the shielding gas flow rate increases from 0 to 45 SCFH. However, the hardness significantly dropped at 65 SCFH. The drop in hardness was attributed to an increase in the presence of porosity. It is postulated that the high shielding gas flow rate resulted in turbulence flow that promotes air entrapment in the weld joint during solidification. The high flow rate also induced rapid solidification of weld joint that reduces the chance of air escaping from the weld pool.